CULTIVATING BIBLICAL LEARNING COMMUNITY IN A VIRTUAL LEARNING ENVIRONMENT THROUGH GROUP PROJECT-BASED LEARNING - Tantu, Year Rezeki Patricia; Silitonga, Bertha Natalina; Tangkin, Wiyun Philipus (Universitas Pelita Harapan, 2022)
For the last two years, the Covid-19 pandemic has caused students to learn in a virtual mode, cultivating a learning community that fully supports students is therefore particularly challenging. Studies have proved that in a virtual learning environment there is a greater possibility of learning loss including loss of learning about and through interaction and relationship values. From a Biblical perspective, relationship in the learning community needs to be built, repaired, and maintained to make learning fruitful, constructive, and meaningful to students. Therefore, strategies for building this learning community are required in virtual classrooms to help students learn effectively. This study focuses on the experiences of how the biblical learning community is cultivated through an iterative process in group project-based learning. This study uses a qualitative descriptive method on cohort-2020 primary student-teachers at Teachers College, Pelita Harapan University. The data was obtained from observation, performance rubric, and questionnaire. Results from the performance rubric showed that around 65-66% of total students have consideration for the feelings and learning needs of other members in his/her group and encourage others to contribute, and 73-74% of total students show solid cooperation in the group. In addition, data from observation and questionnaires indicated that few students still need time to develop those abovementioned aspects. Bahasa Indonesia AbstrakPandemi Covid-19 yang sudah terjadi selama dua tahun terakhir ini telah menyebabkan siswa belajar dalam sebuah mode virtual, mengkultivasi sebuah komunitas belajar yang sepenuhnya mendukung mereka adalah hal yang menantang. Penelitian-penelitian telah membuktikan bahwa di dalam sebuah lingkungan pembelajaran virtual, terdapat kemungkinan yang lebih besar untuk terjadinya kehilangan pembelajaran, termasuk kehilangan pembelajaran tentang dan melalui nilai-nilai interaksi dan hubungan. Dari perspektif Alkitabiah, hubungan di dalam komunitas belajar perlu dibangun, diperbaiki, dan dipelihara untuk membuat pembelajaran berbuah, konstruktif, dan bermakna bagi para siswa. Oleh karena itu, strategi untuk membangun komunitas belajar ini diperlukan dalam ruang kelas virtual untuk membantu siswa belajar secara efektif. Penelitian ini berfokus pada pengalaman tentang bagaimana komunitas belajar yang alkitabiah dikultivasi melalui sebuah proses berulang dalam pembelajaran berbasis proyek grup. Penelitian ini menggunakan metode kualitatif deskriptif pada mahasiswa-guru angkatan 2020 di Teachers College, Universitas Pelita Harapan. Datanya diperoleh dari observasi, rubrik performa, dan kuesioner. Hasil dari rubrik performa menunjukkan bahwa sekitar 65–66% dari keseluruhan siswa memiliki perhatian untuk perasaan dan kebutuhan belajar anggota-anggota lain dalam grupnya, juga mendorong siswa-siswa lain untuk berkontribusi dan 73–74% dari keseluruhan siswa menunjukkan kerja sama yang solid dalam grup. Selain itu, data dari observasi dan kuesioner mengindikasi bahwa beberapa siswa masih membutuhkan waktu untuk mengembangkan aspek-aspek yang disebutkan di atas.